EKSPLORASI VARIABEL PENENTU IMPULSE BUYING DENGAN PENDEKATAN FACTORING ANALYSIS - Sri - Widiyati (Politeknik Negeri Semarang, 2015)
Impulse purchase or impulse buying describesany purchase which shopper makes, throughit was not planned in advance. The goal of theresearch is to find out the factors that affectstudents impulse buying behavior inSemarang. The impact of various variableslike window display, lay out, display ofproduct, sales discount, promotion,time andmoney, peer group, behavior of sales personhas been analyzed. The sample size was 30students and collecting by using purposivesampling with one condition that student oncetime per month shopping at Mall. Thestatistical analysis method employed in thisstudy are validity, realibility, factoring.Factoring analysis used to extract factors.Based on the result of Factoring analysis , itis found that the impulse buying ofcommodities is on a great rise mainly due toin-store shopping evironment ; pricingstrategy ; time and money.